Pengetahuan dan Sikap terhadap Perilaku Penerapan Protokol Kesehatan untuk Pencegahan COVID-19 bagi Pelaku Pasar - Yusrawati Yusrawati; Mawar Hayati (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the relationship between knowledge and attitudes towards the behavior of traditional market participants regarding the prevention of the spread of the COVID-19 virus at the Lhokseumawe City Market Center. The research design used in this study is a cross-sectional study. The results showed that most of the respondents' knowledge was in the sound and good category, as many as 82 (68.3%), and the respondents' attitudes were mainly in the excellent and sufficient class, as many as 68 (56.7%). Most of the respondent's behavior was in an outstanding category, with as many as 53 (51.0%). In conclusion, there is a relationship between knowledge and attitudes towards traditional market players regarding preventing the spread of the COVID-19 virus at the Lhokseumawe City Market Center. Keywords: Market participants, Knowledge, Behavior, Health Protocol, Attitude